Well supplied in life, set aside in death: A multi-isotope study of Justinian plague victims from Saint-Doulchard (France, 7th-8th centuries AD) - Vytlačil, Zdeněk; Durand, Raphaël; Kacki, Sacha; Holleville, Marion; Drtikolová Kaupová, Sylva; Brůžek, Jaroslav; Castex, Dominique; Velemínský, Petr (American journal of biological anthropology, 2024)
OBJECTIVES: Justinian plague and its subsequent outbreaks were major events influencing Early Medieval Europe. One of the affected communities was the population of Saint-Doulchard in France, where plague victim burials were concentrated in a cemetery enclosure ditch. This study aimed to obtain more information about their life-histories using the tools of isotope analysis. MATERIALS AND METHODS: Dietary analysis using carbon and nitrogen isotopes was conducted on 97 individuals buried at Le Pressoir in Saint-Doulchard, with 36 of those originating from the enclosure ditch. This sample set includes all individuals analyzed for plague DNA in a previous study. Mobility analysis using strontium isotope analysis supplements the dietary study, with 47 analyzed humans. The results are supported by a reference sample set of 31 animal specimens for dietary analysis and 9 for mobility analysis. RESULTS: The dietary analysis results showed significantly different dietary behavior in individuals from the ditch burials, with better access to higher quality foods richer in animal protein. 87Sr/86Sr ratios are similar for both studied groups and indicate a shared or similar area of origin. DISCUSSION: The results suggest that the ditch burials contain an urban population from the nearby city of Bourges, which overall had a better diet than the rural population from Saint-Doulchard. It is implied that city's population might have been subjected to high mortality rates during the plague outbreak(s), which led to their interment in nearby rural cemeteries.
Keywords: dospělí; Animals; Female; Infant; izotopy uhlíku; dítě; předškolní dítě; Adult; Plague; Nitrogen Isotopes; mladý dospělý; ženské pohlaví; Adolescent; History, Medieval; Strontium Isotopes; Carbon Isotopes; lidé; Early Middle Ages; Francie; Justinian plague; δ13C; δ15N; dieta; Male; Diet; kojenec; Young Adult; Child, Preschool; dějiny středověku; izotopy dusíku; Cemeteries; hřbitovy; France; 87Sr/86Sr; lidé středního věku; Child; mužské pohlaví; zvířata; Middle Aged; mladiství; izotopy stroncia; mor; Humans